The Students’ Ability in Reading Comprehension in Narrative Text - Sembiring, Rony Arahta (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2019)
Reading skill plays an important role in English learning process, especially when student have to deal with TOEFL Exam which includes reading and writing skill. The writer observed that the process of comprehending a reading text was still a serious problem for the students. The writer applied a qualitative method in this research with descriptive approach. The subject of the study was the first semester students class E of Universitas Prima Indonesia Medan. The instrument of data collecting was multiple choice test. The mean score of the students’ in comprehending narrative text was 77. It shown that their comprehension narrative text was average to good. There was 12 students (48%) was classified as Excellent, 12 students (48%) was classified as Good and there was 1 students (4%) was classified as Average whereas no student (0%) was classified as poor to comprehending narrative text. Therefore, the writer hopes that the other English lecturer should always try to create an interesting text and media for their teaching.